Characterizing cortical hemodynamic changes during climbing and its relation to climbing expertise - Carius, D.; Hörnig, L.; Ragert, P.; Kaminski, E. (Neuroscience Letters, 2020)
Highlights • Functional near-infrared spectroscopy during bouldering produces functional data.